N-(2-Chloro-4-nitrophenyl)-2-nitrobenzamide - Saeed, Aamer (International Union of Crystallography, 2008)
In the title compound, C(13)H(8)ClN(3)O(5), the dihedral angle between the two aromatic rings is 70.74 (6)°. The nitro groups of the Cl-substituted and benzamide benzene rings are twisted by 2.6 (1) and 31.3 (2)°, respectively. The crystal packing shows intermolecular C—H⋯O hydrogen bonds that link molecules into sheets stacked along [010].